Wetlands - Worth for Singhara (Trapa spp.) Cultivation - Singh, Jitendra; Kaushik, R. A.; Chauhan, P. S.; Jain, S. K.; Kavita, A. (Indian Forester, 2011)
Singhara cultivation is an important option for the rural families in neglected wetlands as a profitable venture. Its cultivation is sure to add rural employment opportunity and to render additional income to the growers.